Author Correction: Cluster-assembled zirconia substrates promote long-term differentiation and functioning of human islets of Langerhans. Issue 1 (December 2018) - Galli, Alessandra; Maffioli, Elisa; Sogne, Elisa; Moretti, Stefania; Cairano, Eliana; Negri, Armando; Nonnis, Simona; Norata, Giuseppe; Bonacina, Fabrizia; Borghi, Francesca; Podestà, Alessandro; Bertuzzi, Federico; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.